2009
DOI: 10.1097/brs.0b013e3181a3c7a2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Melatonin and Calmodulin in Paravertebral Muscle and Platelets of Patients With or Without Adolescent Idiopathic Scoliosis

Abstract: AIS group had an asymmetric distribution of calmodulin in paraspinal muscle, higher at the convex side and lower at the concave. Neither platelet melatonin nor platelet calmodulin was found to be representative of the muscle protein values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 19 publications
0
40
1
4
Order By: Relevance
“…The bipedal rat/mouse model has been extensively used for scoliosis research [18,19,38,39]. However, validity of this model has been questioned by Janssen et al [40].…”
Section: Discussionmentioning
confidence: 99%
“…The bipedal rat/mouse model has been extensively used for scoliosis research [18,19,38,39]. However, validity of this model has been questioned by Janssen et al [40].…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulin, a calcium-binding receptor protein, regulates contractile properties in platelets and muscles, and interacts with melatonin. Increased levels of calmodulin in platelets and an asymmetrical distribution of calmodulin in paraspinal muscles compared to healthy controls have been described in IS patients [18, 19]. …”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…Recently, the possible role of calmodulin (CaM) as a mediator of the melatonin antiscoliosis effects has been proposed [7880]. Melatonin is an inhibitor of calmodulin [81, 82] and, the loss of this inhibition, due to the lack of melatonin, could be the cause of scoliosis in these animal models.…”
Section: Melatonin and Adolescent Idiopathic Scoliosis (Ais)mentioning
confidence: 99%
“…In a similar study, carried out on C57BL6 mice (which are genetically melatonin deficient), it was observed that they develop scoliosis when rendered bipedal; in these animals as well, tamoxifen improved the scoliosis deformities. In humans, Acaroglu et al [78] compared the content of CaM and melatonin in muscle and platelets of scoliotic and healthy populations. The patients suffering with AIS had asymmetric distribution of CaM in the paraspinal muscles, with its concentration being higher at the convex side and lower at the concave curvatures of the spinal column, whereas neither platelet melatonin nor platelet CaM was found to be representative of the muscle protein values.…”
Section: Melatonin and Adolescent Idiopathic Scoliosis (Ais)mentioning
confidence: 99%